Solvent retention capacity and swelling index of glutenin as selection tools in South African bread wheat breeding - Wessels, Roean (University of the Free State, 2018)
To release wheat varieties which comply with strict end-use quality criteria and to deal with the polygenic nature of quality breeding, a breeder needs to be informed of quality potential in early generation populations. This research aimed to determine the use of two small scale rapid tests, solvent retention capacity (SRC) and swelling index of glutenin (SIG) as selection tools for bread wheat quality breeding. Seventeen hard red winter wheat cultivars grown in the dryland summer rainfall region, 22 hard red spring wheat cultivars grown in the irrigated summer rainfall region and nine hard red spring wheat cultivars grown in the winter rainfall region were evaluated with the SRC test requiring a 0.3 g flour sample and the SIG test requiring a 0.04 g flour sample. The relationships of the SRC and SIG parameters with grain, milling, rheological and baking quality-related parameters were determined. Combined ANOVA showed highly significant differences (p≤0.001) among cultivars, environments and cultivar x environment interaction for the measured quality parameters, and the SRC and SIG parameters. Variation between genotypes was large and genotypes contributed significantly to the variance in lactic acid SRC, distilled water SRC, sodium carbonate SRC, sodium bicarbonate SRC, sucrose SRC and lactic acid SIG, indicating the potential of these parameters for selecting improved bread wheat quality. SRC values were significantly (p≤0.001) correlated with bread making quality parameters. The highest correlations were between lactic acid SRC and flour protein content (r=0.67, p≤0.001) in the winter rainfall region and lactic acid SIG and flour protein content (r=0.75, p≤0.001) in the irrigated summer rainfall region. Correlations between SRC, SIG and bread making quality parameters were inconsistent across regions, except for lactic acid SRC and lactic acid SIG with flour protein content and lactic acid SRC, sucrose SRC and lactic acid SIG with alveogram dough strength. Regression coefficients for grain, milling, rheological and baking quality-related characteristics, as predicted by the SRC and SIG parameters, were low to moderately low (12% to 60%), indicating that the SRC and SIG parameters are poor predictors for most of the bread wheat quality parameters in South African wheat. Lactic acid SRC and distilled water SRC were the most common predictor variables, explaining the variation in the models for grain and milling characteristics. Lactic acid SRC, sucrose SRC and lactic acid SIG were responsible for contributing to the variation in most of the models for rheological and baking quality-related characteristics. The alkaline water retention capacity method (sodium bicarbonate SRC) was not effective in predicting bread wheat quality in this study and was initially developed for soft wheat applications. The lactic acid SRC solvent test was the most useful for assessing bread wheat quality in this study and is recommended for the evaluation of hard red winter and spring wheat bread making quality potential.
Dissertation (M.Sc.Agric. (Plant Sciences (Plant Breeding))--University of the Free State, 2018
Keywords: Solvent retention capacity; Swelling index of glutenin; Bread making quality; Wheat flour quality; Hard red wheat; Small scale tests